THE APPLICATION OF SAINTIFIK APPROACH USING CONCRETE OBJECT MEDIA IN IMPROVING OF MATHEMATICS LEARNING ABOUT ADDITION AND SUBTRACTION OF FRACTIONS FOR THE FIFTHGRADE STUDENTS OF SD NEGERI SRUSUHJURUTENGAH IN THE ACADEMIC YEAR OF 2014/2015 - Tama, Firman Adi (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract: The Application of Saintifik Approach Using Concrete Object Media in Improving of Mathematics Learning about Addition And Subtraction of Fractions for the FifthGrade Students of Elementary School. The objectives of the research are: (1) to describe the steps of Saintifik approach using concrete object media, (2) to describe the improvement of Mathematics learning about operations of addition and subtraction of fractions for the fifth grade students of SD Negeri Srusuhjurutengah in the academic year of 2014/2015, and (3) to describe the problems and solutions. This research is a collaborative Classroom Action Research (CAR) conducted in three cycle. Each cycle consisted of planning, implementation, observation, and reflection.  The subjects of this research were 23 students of SD Negeri Srusuhjurutengah in the academic year of 2014/2015. The results of the research show that the application of Scientific approach with concrete object media that implemented with appropriate procedure can improve mathematics learning about operations of addition and subtraction of fractions for the fifth grade students of  SD N Srusuhjurutengah. Keywords: Scientifik, concrete object media, Mathematics